Three new species, two newly recorded species and one newly recorded genus of Lithocolletinae (Lepidoptera: Gracillariidae) from China - Bai, Haiyan; Xu, Jiasheng; Dai, Xiaohua (Zootaxa, 2015)
The Chinese representatives of the genera Chrysaster Kumata and Cameraria Chapman (Gracillariidae: Lithocolletinae) were studied. Chrysaster is recorded for the first time in China. Three species belonging to Cameraria, C. diplodura Bai, sp. nov., C. rhynchophysa Bai, sp. nov. and C. jiulianshanica Bai, sp. nov., are described as new. Chrysaster hagicola Kumata and Cameraria magnisignata Kumata are new records for China. Adults and genitalia of the five species are illustrated. A key to the Chinese species of Cameraria is provided.